Catholic Church in Albay speaks out vs EJK, violence - Arguelles, Mar S. (2017)
Hundreds of Catholic faithful in three cities of Albay province are staging simultaneous prayer rallies on Friday to launch a campaign calling for the end to killings under the Duterte administration.
Keywords: Extrajudicial executions -- Religious aspects -- Catholic Church; Camalig, Albay